Generalized papular-purpuric eruption due to Solenopsis fugax bites - Paolo Romita; Caterina Foti; Mario Principato; Luca Stingeni (Anais Brasileiros de Dermatologia, 2018)
Abstract: A 59-year-old atopic man referred to for the onset of a diffused itching papular-purpuric eruption involving his trunk and legs but without systemic symptoms. History revealed that he started feeling itching after spending few hours in his basement. Direct examination of the environmental dust (www.edpa.it) showed high level of infestation of Solenopsis fugax, a small Myrmicinae ant. The skin eruption completely healed without scarring in 2 weeks. Specific disinfestation measures were performed and the patient did not comply of any recurrence during a 6-months follow-up.